IMPROVING STUDENTS’ LINGUISTIC COMPETENCE IN THE CLASSROOM VIA AUTHENTIC MATERIALS (Conference Zone, 2022)
This article examines the notion of authenticity in language teaching. Based on the definitions of authenticity and related debates of the notion in the existing literature, this paper illustrates that authentic materials could be used in L2 reading classrooms by material adaptation. Implications for teaching are also discussed. Language teachers should understand the notion of authenticity, use authentic materials through graded tasks in class, and keep updated with the notion by learning from the existing literature.